Given "(D^2+5DD'+5D'^2)z= x.sin(3x-2y)"
The auxiliary equation is
"m^2+5m+5=0 \\implies \\frac{-b \\pm \\sqrt{b^2-4ac}}{2a} =\\frac{-5 \\pm \\sqrt{5^2-4(1)(5)}}{2(1)} \\\\\ni.e.\\ m=-5,0\\\\"
whence complementary function (C.F.) =
"\\phi_1(y-5x)+\\phi_2(y)\\\\""P.I. = \\frac{1}{D^2+5DD'+5D'^2}x \\cdot sin(3x-2y)=\n\\begin{cases} \n D^2=-9 \\\\\n DD'=6 \\\\\n D'=-4 \n \\end{cases}"
(i.e., on replacing "D^2" by "a^2,\\ DD'" by "-ab, D'^2=-b^2" provided "\u03c6(\u2013a2, \u2013ab, \u2013b2) \u2260 0" )
Clearly it is a case of failure as "\u03c6(\u2013a2, \u2013ab, \u2013b2) = 0."
Therefore, factorize "\\phi (D,D')" and apply these factors turn by turn
"P.I.=\\frac{1}{D(D+5D')}x\\ sin (3x-2y)\\\\\n=\\frac{1}{D} \\intop_{D+5D'}x\\ sin (3x-10x-2c_1)\\ \\therefore\\ y-5x=c_1\\\\\n=\\frac{1}{D} \\intop x\\ sin (-7x-2c_1)\\delta x =\\frac{1}{D} \\intop \\frac{- x\\ cos (-7x-2c_1)}{-7}+\\frac{1}{-7}\\frac{sin (-7x-2c_1)}{-7}\\\\\n=\\frac{1}{D}\\frac{x}{7}cos(3x-2y)+\\frac{1}{49}sin (3x-2y)\\\\\n= \\intop_D(\\frac{x}{7}cos(3x-2y)+\\frac{1}{49}sin(3x-2y))\\delta x\\\\\n\n= \\intop_D(\\frac{x}{7}cos(3x-2c_2)+\\frac{1}{49}sin(3x-2c_2))\\delta x\\ \\therefore y=c_2\\\\"
"= \\intop(\\frac{x}{7}cos(3x-2c_2)\\delta x+\\intop\\frac{1}{49}sin(3x-2c_2))\\delta x\\"
Letting "a= \\intop(\\frac{x}{7}cos(3x-2c_2)\\delta x" and "b=\\intop\\frac{1}{49}sin(3x-2c_2))\\delta x\\"
"a= \\intop(\\frac{x}{7}cos(3x-2c_2)\\delta x =\\frac{x\\ sin(3x-2c_2)}{21}+\\frac13 \\frac{cos(3x-2c_2)}{3}\\\\\na\\implies \\frac{x}{21}sin(3x-2c_2) +\\frac{1}{9}cos(3x-2c_2)\\\\\n\nb= \\intop(\\frac{1}{49}sin(3x-2c_2)\\delta x =\\frac{-cos(3x-2c_2)}{49}+\\frac13 \\frac{sin(3x-2c_2)}{49}\\\\\nb\\implies -\\frac{1}{49}cos(3x-2c_2) +\\frac{1}{147}sin(3x-2c_2)\\\\\n\n\\therefore a+b \\implies \\frac{x}{21}sin(3x-2c_2) +\\frac{1}{9}cos(3x-2c_2)-\\frac{1}{49}cos(3x-2c_2) +\\frac{1}{147}sin(3x-2c_2)\\\\ \n\n\\implies \\frac{7x}{147}sin(3x-2c_2)+\\frac{1}{147}sin(3x-2c_2) +\\frac{40}{441}cos(3x-2c_2)\\\\ \nP.I. =\\frac{7x}{147}sin(3x-2y)+\\frac{1}{147}sin(3x-2y) +\\frac{40}{441}cos(3x-2y)\\\\"
"\\therefore" The complete Integral "z=C.I.+P.I."
Answer
"=\\phi_1(y-5x)+\\phi_2(y)+\\frac{7x}{147}sin(3x-2y)+\\frac{1}{147}sin(3x-2y) +\\frac{40}{441}cos(3x-2y)\\\\"
Comments
Leave a comment